Go Backward, Save energy: Reversible computing principles point a way toward more efficient computers. - Edwards, Chris (Communications of the ACM, 2022)
The article presents the author's views on the development of reversible computing as a way to improve computer efficiency. It mentions the move toward three-dimensional integration and topics including circuit design, controlling the switch state of metal oxide semiconductors (MOS), and adiabatic computing.